The power of school feeding programmes to improve nutrition - Alderman, Harold; Chakrabarti, Suman; Gilligan, Daniel O.; Menon, Purnima; Scott, Samuel P. (International Growth Centre, 2021)
India has the world’s highest number of undernourished children and the largest school-feeding programme – the Mid-Day Meal (MDM) scheme – but limited evidence is available on the intergenerational impact of the programme. Based on data from the National Family Health Survey and National Sample Survey, this article shows if a mother was a beneficiary of MDM during schooling, there is a 20-30% reduction in height deficits of her children.